Cellulose fibril reinforced repair mortar

Cellulose fibrils in repair mortars improve interfacial bond strength and corrosion resistance, addressing the limitations of traditional cement-based mortars by ensuring uniform distribution and reducing pretreatment needs.

JP7605775B2Active Publication Date: 2024-12-24PERFORMANCE BIOFILAMENTS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021574808
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-24
Filing Date
2020-03-11
Publication Date
2024-12-24
Estimated Expiration
2040-03-11

AI Technical Summary

Technical Problem

Traditional cement-based repair mortars suffer from poor interfacial bond strength with concrete substrates, leading to delamination and corrosion of steel reinforcing bars, and require time-consuming and costly pretreatment processes.

Method used

Incorporation of cellulose fibrils, such as nanofibrillated and microfibrillated cellulose, into the repair mortar to enhance interfacial bond strength and reduce corrosion, with a uniform distribution achieved through specific mixing methods.

Benefits of technology

The cellulose fibril-reinforced repair mortars demonstrate improved adhesion and corrosion resistance, reducing premature delamination and enhancing the long-term durability of repaired concrete structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605775000008
    Figure 0007605775000008
  • Figure 0007605775000009
    Figure 0007605775000009
  • Figure 0007605775000010
    Figure 0007605775000010
Patent Text Reader

Abstract

A repair mortar and a method for preparing the repair mortar are provided. The repair mortar includes a cement binder, fine aggregate, and cellulose fibrils. In some embodiments, the cellulose fibrils are uniformly dispersed throughout the repair mortar. In some embodiments, the cellulose fibrils include nanofibrillated cellulose and / or microfibrillated cellulose. In some embodiments, the cellulose fibrils have an aspect ratio of about 20 to about 500. The method includes mixing a cement binder and fine aggregate with water / chemical admixture to obtain a cementitious material with a good consistency, mixing the cellulose fibrils with water to obtain a cellulose fibril slurry, and mixing the cellulose fibril slurry with a workable cementitious material. In some embodiments, the cellulose fibrils are uniformly dispersed throughout the workable cementitious material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a repair mortar, and in particular to a cellulose fibril reinforced repair mortar that enhances the interfacial bond strength between the repair mortar and a concrete substrate, and minimizes corrosion of steel reinforcing bars embedded in the repaired concrete. [Background technology]

[0002] Concrete is one of the most used building materials due to its good compressive strength and relatively low cost. Unfortunately, concrete is prone to cracking and deterioration, which weakens its structural integrity. Furthermore, corrosion of the rebars in reinforced concrete affects the durability of such structures. The main cause of corrosion is the high permeability of some concretes. This allows water, oxygen, chlorides, and other corrosive substances to penetrate the concrete matrix and corrode the embedded steel reinforcing bars.

[0003] Cement-based repair mortars are commonly used to repair cracked or deteriorated concrete and / or fill concrete honeycombs. Traditional cement-based repair mortars include a binder (e.g., cement), a filler (e.g., sand, gravel, calcium carbonate, limestone aggregate, etc.), a bond enhancer (e.g., powdered polymer), and a hydrating agent (e.g., water). However, cement-based repair mortars have drawbacks such as cracking during initial curing and / or spalling caused by poor adhesion at the interface between the repair mortar and the concrete. Statistics presented by Tilly and Jacobs (Tilly and Jacobs, Concrete Repairs, Performance in Service and Current Practice, HIS BRE Press, Bracknell, 2007) suggest that 20%, 55%, and 90% of cement-based repair materials fail within 5, 10, and 25 years, respectively. 80% of failures of cement-based patch repairs are due to problems related to delamination, cracking, and corrosion due to poor interfacial bond strength between the cement-based repair mortar and the concrete.

[0004] The interfacial bond strength of the mortar-concrete interface is affected by at least two factors: (1) the surface condition of the concrete, and (2) the curing conditions of the cement-based mortar. Regarding the surface condition of the concrete, the concrete may be pretreated. Pretreatment typically involves one or more of scarifying, roughening, and conditioning the surface of the concrete to be repaired before applying the repair mortar. For example, the International Concrete Repair Institute (ICRI) recommends specific concrete surface roughening and provides preparation and evaluation techniques (ICRI Technical Guideline No. 310.2R-2013; Formerly Guidelines No. 03732: Selecting and Specifying Concrete Surface Preparation for Coatings, Sealers, and Polymer Overlays, ICRI 310.2R-2013, Minnesota, 2013). However, pretreatment typically requires time, energy, and cost. In addition, weather, urgency, and other external factors may affect pretreatment.

[0005] Regarding the curing conditions of cement-based mortar, the initial volume change and associated shrinkage stress generation may cause defects in the curing mortar. During curing, the old dry concrete absorbs moisture from the cement-based mortar. This may cause "false setting" (i.e., rapid hardening of the repair mortar) which may cause the mortar to dry out and form loose powder at the repair mortar / concrete interface (i.e., efflorescence). As a result, the interfacial bond strength between the cement-based repair mortar and the old concrete may be compromised, resulting in delamination.

[0006] Furthermore, cement-based composites shrink as they harden. Therefore, the volume of a hardened (i.e., non-workable) cement-based mortar overlay is typically smaller than its volume immediately after casting. Cement-based composites are workable and capable of shrinking during the initial stages of mixing and casting. However, as the cement-based composite hardens and develops strength, its ability to shrink decreases. Lack of moisture leads to autogenous shrinkage deformation and associated matrix cracking, especially for cement-based composites with low water:cement ratios. Previous studies have shown that the inclusion of water-retentive porous materials (e.g., lightweight aggregates (LWA) and superabsorbent polymers (SAP)) in the mixture can reduce the initial autogenous deformation of cement composites (Jensen & Hansen., 2002; Bentz, 2007; Castro et al., 2011). However, considering the attributes of nano- and micro-sized cellulose fibers, such as their wide availability, low density, high specific surface area, and hydrophilicity, they may also function as water-retaining and desorbing agents in cement composites.

[0007] A major challenge in introducing cellulose fibers into a cement-based matrix is ​​achieving uniform fiber dispersion throughout the matrix. Poor fiber dispersion and / or uneven fiber distribution in the cement-based matrix can reduce the structural integrity and / or strength of the composite. Furthermore, the addition of pulp fibers to cement-based composites generally impairs the workability and casting time of the composite. Thus, a higher water or superplasticizer content is often required to improve the workability and increase the casting time of the composite. Adding extra water typically is avoided because it makes the cement-based material more porous and weaker, generally reducing other performances of the cement composite (mechanical strength, adhesive strength, freeze-thaw properties, etc.).

[0008] Pouring time refers to the time it takes for a cement-based composite to be poured without significant loss of workability. A cement-based composite with significantly reduced workability is not only difficult to compact and finish, but can also contribute to poor adhesion between the composite and the cement-based substrate (e.g., concrete). The desired pouring time allows the user to spread the mortar over a large area without losing consistency (=workability) before the mortar is complete.

[0009] Materials that act as good moisture reservoirs (i.e., by retaining and releasing moisture during cement hydration) without adversely affecting the strength and durability of cement-based composites include superabsorbent polymers (SAPs) and lightweight fine aggregates (LWAs). Unfortunately, these materials are not ideal because they are not cost-effective to use in large-scale applications. SAPs are also dimensionally unstable, which can adversely affect the strength and modulus of cement-based composites.

[0010] Internal hardeners are known that are used to reduce autogenous shrinkage of cement-based composites. Although the use of some of these internal hardeners results in high strength cement-based composites, it does not necessarily follow that the high strength cement-based composites will function as effective, durable, high performance cement-based composites. For example, high strength cement composites are recognized as having superior strength properties. However, when high strength cement mortars are applied to concrete substrates, they lack crack growth resistance at the mortar-concrete substrate interface. Thus, the more brittle high strength cement composites are not effective as repair materials. In other words, the compressive strength of a cement-based material is not indicative of an attribute that defines its performance. Therefore, it is not possible to predict how a cement-based repair mortar will interact with a concrete substrate as it forms an interface between the mortar and the substrate.

[0011] There is a widespread desire for cement-based repair mortars with enhanced overall performance characteristics, including interfacial bond strength between the cement-based repair mortar and the concrete substrate interface, and mitigation of corrosion of steel reinforcing bars in repaired reinforced concrete structures. It is desirable for such repair mortars to be composed of sustainable, environmentally friendly, and renewable materials.

[0012] The foregoing examples of the related art and limitations associated therewith are intended to be illustrative, not exhaustive. Other limitations of the related art will become apparent to those of ordinary skill in the art upon reading this specification and studying the drawings. Summary of the Invention

[0013] The following embodiments and aspects thereof are described and illustrated in conjunction with representative and exemplary systems, means, and methods that are not intended to be limiting in scope. In various embodiments, one or more of the above problems are reduced or eliminated, while other embodiments are directed to other improvements.

[0014] The present invention relates to a repair mortar that can enhance the interfacial bond strength between a repair mortar overlay and a concrete substrate. The repair mortar described herein provides the final repair product with one or more of improved rebar corrosion resistance, reduced initial deformation, and enhanced interfacial bond strength between the repair mortar overlay and a concrete substrate, as compared to conventional mortars.

[0015] One embodiment of the present invention provides a repair mortar comprising a cement binder and cellulose fibrils.

[0016] In some embodiments, the cellulose fibrils are uniformly dispersed throughout the repair mortar.

[0017] In some embodiments, the cellulose fibrils comprise nanofibrillated cellulose and / or microfibrillated cellulose.

[0018] In some embodiments, the aspect ratio of the cellulose fibrils is from about 20 to about 500.

[0019] In some embodiments, the width of the cellulose fibrils is from about 20 nm to about 30 μm.

[0020] In some embodiments, the length of the cellulose fibrils is from about 1 μm to about 2,000 μm.

[0021] In some embodiments, the cellulose fibrils comprise from about 0.05 vol.% to about 5 vol.% of the repair mortar.

[0022] In some embodiments, the cellulose fibrils comprise about 0.1 vol.% of the repair mortar.

[0023] In some embodiments, the surface area of ​​the cellulose fibrils is about 80 m 2 In another embodiment, the surface area of ​​the cellulose fibrils is 60 to 100 m 2 / g.

[0024] In some embodiments, the water retention value (WRV) of the cellulose fibrils is from about 2 to about 5.

[0025] In some embodiments, the density of the cellulose fibrils is about 1,300 kg / m 3 ~Approx. 1,500kg / m 3 It is.

[0026] In some embodiments, the viscosity of the cellulose fibrils is from about 1,000 mL / g to about 5,000 mL / g.

[0027] In some embodiments, the cement binder comprises one or more of aluminous cement, blast furnace cement, calcium aluminate cement, type I portland cement, type IA portland cement, type II portland cement, type IIA portland cement, type III portland cement, type IIIA portland cement, type IV portland cement, type V portland cement, hydraulic cement (e.g., white cement, gray cement, blended hydraulic cement, type IS portland blast furnace slag cement, types IP and P portland pozzolanic cement, and type I(SM) slag modified portland cement), blended hydraulic cement, type GU type, HE type early strength cement, medium sulfate resistant cement, type HS type high sulfate resistant cement, type MH moderate heat cement, type LH low heat cement, type K expansive cement, type O expansive cement, type M expansive cement, type S expansive cement, regulated set cement, ultra early strength cement, high iron cement, and oil well cement.

[0028] In some embodiments, the cement binder comprises about 20 vol.% to about 22 vol.% of the repair mortar.

[0029] In some embodiments, the repair mortar has a water:cement binder ratio of about 0.2 to about 0.6.

[0030] In some embodiments, the cement binder comprises one or more of a filler, a chemical admixture, and a water retention agent.

[0031] In some embodiments, the filler comprises one or more of sand, calcium carbonate, limestone, crushed stone, and gravel.

[0032] In some embodiments, the filler comprises about 45 vol.% to about 55 vol.% of the repair mortar.

[0033] In some embodiments, the chemical admixture comprises one or more of an air entrainer, a retarder, an accelerator, a plasticizer, a polymer, a corrosion inhibitor, an alkali-silica reactivity inhibitor, a binder, a colorant, a defoamer, an odor remover, and a dry dispersant.

[0034] In some embodiments, the chemical admixture comprises about 0.03 vol.% to about 0.3 vol.% of the repair mortar.

[0035] In some embodiments, the water retention agent comprises a copolymer.

[0036] In some embodiments, the copolymer comprises one or more of hydroxypropyl methylcellulose (HPMC), hydroxyethyl methylcellulose (HEMC), welan gum, and xanthan gum.

[0037] In some embodiments, the water retention agent comprises about 0 vol.% to about 0.08 vol.% of the repair mortar.

[0038] Another aspect of the invention provides a method of preparing a repair mortar, the method comprising mixing a cement binder with water and chemical admixtures to obtain a workable cementitious material, and then adding a cellulose fibril slurry to the premixed cementitious material. In some embodiments, mixing the cellulose fibril slurry with the workable cementitious material comprises uniformly dispersing the cellulose fibrils throughout the workable cementitious material.

[0039] Another aspect of the invention provides a method of preparing a repair mortar, the method comprising: mixing a cement binder with a water / chemical admixture to obtain a workable cementitious material; and mixing cellulose fibrils with the workable cementitious material. In some embodiments, mixing the cellulose fibrils with the workable cementitious material comprises uniformly dispersing the cellulose fibrils throughout the workable cementitious material.

[0040] Another aspect of the invention provides a method of preparing a repair mortar, comprising mixing a cement binder with cellulose fibrils to uniformly disperse the cellulose fibrils throughout the cement binder, and mixing the cement binder and cellulose fibrils with a water / chemical admixture to obtain a repair mortar with a very good consistency.

[0041] In some embodiments, the cellulose fibrils comprise nanofibrillated cellulose and / or microfibrillated cellulose.

[0042] In some embodiments, the aspect ratio of the cellulose fibrils is from about 20 to about 500.

[0043] In some embodiments, the width of the cellulose fibrils is from about 20 nm to about 30 μm.

[0044] In some embodiments, the length of the cellulose fibrils is from about 1 μm to about 2,000 μm.

[0045] In some embodiments, the cellulose fibrils comprise from about 0.05 vol.% to about 5 vol.% of the repair mortar.

[0046] In some embodiments, the cellulose fibrils comprise about 0.1 vol.% of the repair mortar.

[0047] In some embodiments, the surface area of ​​the cellulose fibrils is about 80 m 2 In another embodiment, the surface area of ​​the cellulose fibrils is 60 to 100 m 2 / g.

[0048] In some embodiments, the water retention value (WRV) of the cellulose fibrils is from about 2 to about 5.

[0049] In some embodiments, the density of the cellulose fibrils is about 1,300 kg / m 3 ~Approx. 1,500kg / m 3 It is.

[0050] In some embodiments, the viscosity of the cellulose fibrils is from about 1,000 mL / g to about 5,000 mL / g.

[0051] In some embodiments, the cement binder comprises one or more of aluminous cement, blast furnace cement, calcium aluminate cement, type I portland cement, type IA portland cement, type II portland cement, type IIA portland cement, type III portland cement, type IIIA portland cement, type IV portland cement, type V portland cement, hydraulic cement (e.g., white cement, gray cement, blended hydraulic cement, type IS portland blast furnace slag cement, types IP and P portland pozzolanic cement, and type I(SM) slag modified portland cement), blended hydraulic cement, type GU type, HE type early strength cement, medium sulfate resistant cement, type HS type high sulfate resistant cement, type MH moderate heat cement, type LH low heat cement, type K expansive cement, type O expansive cement, type M expansive cement, type S expansive cement, regulated set cement, ultra early strength cement, high iron cement, and oil well cement.

[0052] In some embodiments, the cement binder comprises about 20 vol.% to about 22 vol.% of the repair mortar.

[0053] In some embodiments, the repair mortar has a water:cement binder ratio of about 0.2 to about 0.6.

[0054] In some embodiments, the method further includes mixing one or more of a filler, a chemical admixture, and a water retention agent with one or more of the cement binder and the workable cementitious material.

[0055] In some embodiments, the method further includes mixing one or more of a filler, a chemical admixture, and a water retention agent with a third liquid to obtain a liquid mixture, and adding the liquid mixture to one or more of the workable cementitious material and the cellulose fibril slurry.

[0056] In some embodiments, the filler comprises one or more of sand, calcium carbonate, limestone, crushed stone, and gravel.

[0057] In some embodiments, the filler comprises about 45 vol.% to about 55 vol.% of the repair mortar.

[0058] In some embodiments, the chemical admixture comprises one or more of an air entrainer, a retarder, an accelerator, a plasticizer, a polymer, a corrosion inhibitor, an alkali-silica reactivity inhibitor, a binder, a colorant, a defoamer, an odor remover, and a dry dispersant.

[0059] In some embodiments, the chemical admixture comprises about 0.03 vol.% to about 0.3 vol.% of the repair mortar.

[0060] In some embodiments, the water retention agent comprises a copolymer.

[0061] In some embodiments, the copolymer comprises one or more of hydroxypropyl methylcellulose (HPMC), hydroxyethyl methylcellulose (HEMC), welan gum, and xanthan gum.

[0062] In some embodiments, the water retention agent comprises about 0 vol.% to about 0.08 vol.% of the repair mortar.

[0063] Another aspect of the invention provides a method of repairing a concrete substrate, the method comprising applying to a surface of the concrete substrate a repair mortar comprising a cement binder, fine aggregate, and cellulose fibrils.

[0064] In some embodiments, the method further comprises pretreating a surface of the concrete substrate.

[0065] Another aspect of the present invention provides the use of a repair mortar comprising a cement binder, fine aggregate and cellulose fibrils for repairing cracked and / or deteriorated concrete materials.

[0066] In some embodiments, the use of the repair mortar is to fill one or more cavities or voids in a concrete material.

[0067] Another aspect of the invention provides a kit for preparing a repair mortar, the kit comprising a first container of cellulose fibrils and a second container of fine aggregate and a cement binder.

[0068] In addition to the exemplary aspects and embodiments described above, further aspects and embodiments will become apparent by reference to the drawings and by study of the following detailed descriptions.

[0069] Exemplary embodiments are illustrated in the referenced figures in the drawings. The embodiments and drawings disclosed herein are intended to be considered illustrative and not limiting. [Brief description of the drawings]

[0070] [Figure 1] This is the chemical structure of the repeating unit (n) of cellulose. [Diagram 2] 1 is a flow chart illustrating a method of preparing a repair mortar in accordance with an example embodiment of the present invention. [Diagram 3] FIG. 2 shows the hydration domains of non-fibrillated pulp fibers (left) and cellulose fibrils (right). [Figure 4] FIG. 1 is a side cross-sectional view of a cylinder composed of a half-cylinder of concrete substrate and a half-cylinder of cement-based repair mortar. [Diagram 5]1 is a graph showing the results of diagonal shear tests performed on cylinders composed of a half-cylinder of steel fiber reinforced concrete substrate with or without cellulose fibrils and a half-cylinder of cement-based repair mortar. [Figure 6] 1 is a graph showing the results of diagonal shear tests performed on cylinders composed of a half-cylinder of unreinforced concrete substrate with or without cellulose fibrils and a half-cylinder of cement-based repair mortar. [Figure 7] FIG. 6 is an image of the cylinder pure compression tested in FIG. 5. [Figure 8] FIG. 7 is an image of the cylinder pure compression tested in FIG. 6. [Figure 9] FIG. 1 is a graph showing the results of diagonal shear tests performed on a cylinder consisting of a half-cylinder of steel reinforced concrete substrate with or without cellulose fibrils and a half-cylinder of cement-based repair mortar, where the surface of the concrete substrate was not pretreated. [Figure 10] FIG. 1 is a graph showing the results of diagonal shear tests performed on cylinders consisting of a half-cylinder of unreinforced concrete substrate with or without cellulose fibrils and a half-cylinder of cement-based repair mortar, where the surface of the concrete substrate was not pretreated. [Figure 11] FIG. 10 is an image of the cylinder pure compression tested in FIG. [Figure 12] FIG. 11 is an image of the cylinder pure compression tested in FIG. [Figure 13(a)] Images of CMFs obtained from multi-stage refining of bleached kraft pulp of 30% consistency, with micro- to nano-size distribution, with fibril widths ranging from 80 nm to 500 nm and lengths ranging from 100 μm to 800 μm. [Figure 13(b)] This is an image of 13mm brass coated steel microfiber. [Figure 13(c)] This is an image of 50mm hook end steel fiber. [Figure 14(a)] FIG. 2 is a cross-sectional view of a cylinder for corrosion testing. [Figure 14(b)] FIG. 14(b) is a top perspective view of the corrosion test cylinder shown in FIG. [Figure 15] FIG. 1 is a schematic diagram of the corrosion test setup. [Figure 16(a)] 1 is an image of a cylindrical specimen for corrosion testing. [Figure 16(b)] 13 is an image of a split corrosion test cylinder specimen covered with reference repair mortar. [Figure 16(c)] 1 is an image of a split corrosion test cylinder coupon covered with repair mortar according to one embodiment of the present invention. [Figure 17] 1 is a graph showing the corrosion current during corrosion testing performed on unreinforced test cylinders of concrete substrates. [Figure 18] 1 is a graph showing the corrosion current during corrosion tests performed on test cylinders with a concrete substrate reinforced with steel fibers. [Figure 19] 1 is a graph showing the time to crack during corrosion testing performed on test cylinders. [Figure 20] 1 is a graph showing crack width over time during corrosion testing performed on test cylinders. [Figure 21] 1 is a graph showing the corrosion rate during corrosion tests performed on test cylinders. [Figure 22] 1 is a graph showing the pull-out force before and after corrosion testing performed on test cylinders. [Figure 23(a)] FIG. 2 is a cross-sectional view of a prism for corrosion testing. [Figure 23(b)] FIG. 23(b) is a top perspective view of the corrosion test prism shown in FIG. 23(a). [Figure 24(a)] 1 is an image of a prism specimen for corrosion testing. [Figure 24(b)] 13 is an image of a split prism corrosion test specimen covered with reference repair mortar after a 15V test. [Figure 24(c)] 13 is an image of a split prism corrosion test coupon covered with repair mortar according to an embodiment of the present invention after 15V testing. [Figure 24(d)]13 is an image of a split prism corrosion test specimen covered with reference repair mortar after 25V testing. [Figure 24(e)] 13 is an image of a split prism corrosion test coupon covered with repair mortar according to an embodiment of the present invention after 25V testing. [Diagram 25] 1 is a graph showing the corrosion current during corrosion tests performed on test prisms at 7.5 V. [Figure 26] 1 is a graph showing the corrosion current during corrosion tests performed on a test prism at 15V. [Figure 27] 1 is a graph showing the corrosion current during corrosion tests performed on a test prism at 25V. [Figure 28] 1 is a graph showing the time to crack during corrosion testing performed on test prisms. [Figure 29] 1 is a graph showing the corrosion rate during corrosion tests performed on test prisms. [Diagram 30] 1 is a graph showing the pull-out force before and after corrosion testing performed on test prisms. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0071] Throughout the following description, specific details are set forth to enable those skilled in the art to gain a deeper understanding. However, well-known elements may not have been shown or described in detail to avoid unnecessarily obscuring the present disclosure. Accordingly, the specification and drawings are to be regarded as illustrative rather than restrictive.

[0072] Unless otherwise specified by context, "concrete" (as used herein) refers to a building material made from a mixture of a binder (e.g., cement, etc.), one or more fillers (e.g., sand, calcium carbonate, limestone aggregate, etc.), and a liquid (e.g., water, etc.). Water retention agents may be added to the mixture.

[0073] Unless the context dictates otherwise, "concrete substrate" (as used herein) refers to set and hardened (i.e., non-workable) concrete to which the repair mortar will adhere.

[0074] Unless the context requires otherwise, "repair mortar" (as used herein) refers to a construction covering a concrete substrate to repair cracked and / or deteriorated concrete substrates and / or to fill voids in deteriorated concrete substrates.

[0075] Unless the context indicates otherwise, "pulp fibers" (as used herein) refers to non-fibrillated cellulosic, hemicellulosic, and lignocellulosic fibers.

[0076] Unless the context dictates otherwise, "cellulose" (as used herein) refers to a carbohydrate polymer containing a chain of glucose units, all of which are β-linked at positions 1 to 4. The structure of cellulose is shown in Figure 1.

[0077] Unless otherwise indicated by context, "cellulosic material" (as used herein) includes, but is not limited to, cellulose fibers derived from one or more of hardwoods, softwoods, agricultural materials (e.g., crop residues including, but not limited to, wheat straw, barley straw, and corn stalks, and fibrous materials including cotton, hemp, flax, jute, and sisal), algal cellulose, marine plant cellulose, hemicellulose fibers, lignocellulosic fibers, pulp fibers, kraft fibers, thermomechanical pulp (TMP) fibers, and one or more of their derivatives including, but not limited to, one or more derived pulp fibers (including, but not limited to, one or more of mechanical, thermomechanical, chemi-thermomechanical, chemical, recycled, and organosolv pulps).

[0078] Unless otherwise specified by context, "cellulose fibril(s)" or "CMF" (as used herein) refers to a cellulosic material that has been fibrillated by converting at least about 25% of the mass of the cellulosic material into nanoscale and / or microscale fibrillated regions. In certain embodiments, the cellulose fibrils include, but are not limited to, nanofibrillated cellulose (also known as cellulose nanofibrils) and / or microfibrillated cellulose (also known as cellulose microfibrils). In certain embodiments, the cellulose fibrils are composed of a mixture of linear and branched cellulose fibrils. In certain embodiments, the cellulose fibrils are in a form in which the fibrils are loose and individual. In such embodiments, the cellulose fibrils are dispersed and not aggregated / cornified / bonded together.

[0079] Unless the context requires otherwise, "workable" (as used herein) refers to the physical properties of freshly mixed concrete or freshly mixed cement-based composites (e.g., cement-based repair mortar). Fresh concrete (or other fresh cement-based composites) are said to be workable if they can be easily mixed, poured, and / or compacted. Concrete (or other cement-based composites) are said to be unworkable if they cannot be mixed, poured, and compacted without segregation (i.e., loss of homogeneity).

[0080] Unless the context indicates otherwise, "hydrophobic" (as used herein) refers to the ability to repel water and / or the ability to not mix with water.

[0081] Unless the context indicates otherwise, "hydrophilic" (as used herein) refers to the ability to attract water and / or to be miscible with water.

[0082] Unless the context requires otherwise, "polymer" (as used herein) refers to a molecule or macromolecule formed by polymerization of smaller molecules called monomers, often, but not always, in the form of a repeating structure.

[0083] Unless the context requires otherwise, "volume percent" (vol.%) (as used herein) refers to the volume of a mixture based on the total volume (v tot ) and is defined as follows: Volume percent = v1 / v tot ×100% In repair mortars, "vol.%" refers to the total dry volume of the mixture (v tot ) refers to the ratio of the dry volume (v1) of a substance to the total volume (v2).

[0084] Unless the context requires otherwise, "weight percent" (wt%) (as used herein) refers to the total mass (m tot ) and is defined as follows: Weight percent = m1 / m tot ×100% In repair mortar, wt% is the total dry weight of binder in the mixture (m tot ) to the dry mass (m1) of a substance.

[0085] Unless the context requires otherwise, "surface area" (as used herein) refers to the measurement of the exposed area of ​​an object expressed in square units.

[0086] Unless the context indicates otherwise, "aspect ratio" (as used herein) refers to the ratio of the size of a cellulose fibril in its length and width dimensions and is defined as follows: Aspect ratio = length / width

[0087] Unless otherwise specified by context, "water retention capacity" (or "WRV") (as used herein) refers to a measure of the ability of cellulose fibrils to retain water. The WRV value is equal to the ratio of the liquid mass of wet cellulose fibrils to the mass of dry cellulose fibrils and is defined as follows: WRV=m 液体 / m 乾燥

[0088] Unless the context dictates otherwise, "slurry" (as used herein) refers to a semi-liquid mixture. The mixture may be colloidal.

[0089] Unless the context requires otherwise, "internal relative humidity" (as used herein) refers to the relative ratio of the amount of liquid and / or liquid vapor within the pores of the repair mortar to the maximum amount of liquid and / or liquid vapor that the pores of the repair mortar can hold at a given temperature and pressure.

[0090] Unless otherwise specified by context, "aggregate" (as used herein) refers to a particular filler material used in cement-based composites. Examples of aggregates include (but are not limited to) sand, gravel, crushed stone, recycled concrete, and geosynthetic aggregates. Typically, coarse aggregates have a diameter of about 5 mm to about 20 mm. In some embodiments, fine aggregates (sand) have a diameter of less than about 5 mm. In some embodiments, gravel has a diameter of about 10 mm or less.

[0091] Unless the context dictates otherwise, "about" (as used herein) means in the vicinity of the stated value (i.e., within ±5% of the stated value).

[0092] Some embodiments provide a repair mortar that can enhance compatibility between the repair mortar overlay and the concrete substrate, thereby enhancing the interfacial bond strength between the repair mortar and the substrate. The repair mortar is reinforced with cellulose fibrils. In some embodiments, the cellulose fibrils represent a low volume fraction of the repair mortar (e.g., about 0.05 vol.% to about 5 vol.% cellulose fibrils). Time-consuming, energy-intensive, and costly pretreatment of the substrate can be avoided by using the repair mortar without compromising the quality of the repair and / or the interfacial bond strength between the repair mortar and the substrate. Premature delamination of the repair material is reduced or eliminated, improving the long-term durability and / or performance of the repaired concrete substrate.

[0093] Several studies have investigated the benefits of adding cellulose nano- and microfibers to cement-based materials (Nilsson and Sargenius, 2011; Mejdoub et al., 2016; Onuaguluchi et al., 2014; Hisseine et al., 2018; Balea 2019), but these studies show that adding cellulose fibers reduces the porosity of the cement-based material. Although low porosity enhances strength and modulus, it makes the repair mortar inadequate due to lack of dimensional compatibility with the substrate and easy delamination (Emmons et al. 1993). Nevertheless, the present inventors have determined that the addition of cellulose fibrils to the cement-based repair mortar described herein surprisingly mitigates these shortcomings. This is due, at least in part, to the unexpected electrochemical compatibility between the cement-based repair mortar of the present invention and concrete substrates, including rebar, in addition to the reasons described elsewhere in this disclosure. Without being bound by any theory, the inventors believe that the unexpected enhanced electrochemical compatibility is due to at least the specific size ranges, surface areas of the added cellulose fibrils, and / or the proportion of cellulose fibrils having specific aspect ratios as described herein.

[0094] The repair mortar described herein comprises a dry mixture or slurry of cellulose fibrils and a cement binder. In some embodiments, the dry cellulose fibrils and the dry cement binder are obtained together or separately and combined with a liquid to form the repair mortar. The cellulose fibrils are obtained as a heterogeneous mixture of cellulose fibrils of various sizes. In some embodiments, the cellulose fibrils are prepared by applying high shear forces to a non-fibrillated cellulose material as known in the art to pull apart the non-fibrillated cellulose fibers. The energy and method of fibrillation applied to the non-fibrillated cellulose material determine the degree of fibrillation. For example, low energy fibrillation of non-fibrillated cellulose fibers initially forms fragmented sheets and / or other aggregates of cellulose nanofibrils and / or cellulose microfibrils. High energy fibrillation forms unified cellulose nanofibrils and / or cellulose microfibrils.

[0095] The cellulose fibrils described herein enhance the compatibility of the repair mortar with the concrete substrate and enhance the interfacial bond strength between the repair mortar and the substrate. Without being bound by any theory, the inventors believe that the aspect ratio of the cellulose fibrils described herein contributes to the enhanced compatibility. In some embodiments, the size distribution of the cellulose fibrils is broad, ranging from about 20 nm to about 30 μm in width and / or from about 1 μm to about 2,000 μm in length, or from about 80 nm to about 500 nm in width and from about 100 μm to about 800 μm in length. In some embodiments, the aspect ratio of the cellulose fibrils is from about 20 to about 500. In some embodiments, the aspect ratio of at least 95% of the cellulose fibrils is at least 50.

[0096] In some embodiments, the surface area of ​​the cellulose fibrils is greater than the surface area of ​​pulp fibers traditionally used to reinforce or reinforce cement-based repair mortars. In some embodiments, the surface area of ​​the cellulose fibrils is greater than about 80 m2 as measured by Brunauer-Emmett-Teller (BET) surface area determination. 2 In another embodiment, the surface area is 60 to 100 m 2 / g.

[0097] The repair mortar requires only a relatively small vol.% of cellulose fibrils. In some embodiments, the repair mortar contains about 0.05 vol.% to about 5 vol.% of cellulose fibrils. In some embodiments, the repair mortar contains about 0.1 vol.% of cellulose fibrils.

[0098] In some embodiments, the combination of aspect ratio and surface area and / or concentration of cellulose fibrils contributes to enhanced compatibility of the repair mortar with the concrete substrate.

[0099] In some embodiments, the WRV and / or surface area of ​​the cellulose fibrils contribute to enhanced compatibility of the repair mortar with the concrete substrate. In some embodiments, the WRV of the cellulose fibrils is greater than the WRV of pulp fibers traditionally used to reinforce or reinforce cement-based repair mortars. In some embodiments, the WRV of the cellulose fibrils is greater than about 2 (i.e., 2 g 水 / g 乾燥 ) to about 5 (i.e., 5 g 水 / g 乾燥 ) range.

[0100] In some embodiments, the viscosity of the cellulose fibrils is from about 1000 mL / g to about 5000 mL / g.

[0101] In some embodiments, the density of the cellulose fibrils is about 1300 kg / m 3~Approx. 1500kg / m 3 is within the range.

[0102] The cement binder may include any cement or mixture of cements or supplemental cementitious materials conventionally known as blended cements. Specific examples of hydraulic cement binders include (but are not limited to) aluminous cements, blast-furnace cements, calcium aluminate cements, American Society for Testing and Materials (ASTM) Designation Type I Portland cement, ASTM Designation Type IA Portland cement, ASTM Designation Type II Portland cement, ASTM Designation Type IIA Portland cement, ASTM Designation Type III Portland cement, ASTM Designation Type IIIA Portland cement, ASTM Designation Type IV Portland cement, ASTM Designation Type V Portland cement, hydraulic cements (e.g., white cement, gray cement, blended cement, etc.), and mixtures of granular cements. Examples of hydraulic cements include ASTM type IS blast furnace slag cement, ASTM type IP and P portland pozzolanic cement, ASTM type I(SM) slag modified portland cement, ASTM type GU blended hydraulic cement, ASTM type HE early strength cement, ASTM type MS medium sulfate resistant cement, ASTM type HS high sulfate resistant cement, ASTM type MH moderate heat cement, ASTM type LH low heat cement, ASTM type K expansive cement, ASTM type O expansive cement, ASTM type M expansive cement, ASTM type S expansive cement, regulated set cement, extra early strength cement, high iron cement, and oil well cement.

[0103] In some embodiments, the repair mortar has a water:cement binder ratio of about 0.2 to about 0.6. In some embodiments, the repair mortar has a water:cement binder ratio of about 0.4 to about 0.6. Conventional concrete has a water:cement binder ratio of about 0.4 to about 0.6. Conventional high performance concrete has a water:cement binder ratio of about 0.2 to about 0.3. Lower water:cement ratios typically result in stronger concrete.

[0104] In some embodiments, the repair mortar comprises about 20 vol.% to about 22 vol.% cement binder.

[0105] In some embodiments, the repair mortar further comprises one or more fillers and / or chemical admixtures. Examples of fillers include (but are not limited to) sand, calcium carbonate, limestone, crushed stone, gravel, and aggregates. Examples of chemical admixtures include (but are not limited to) air entrainers, retarders, accelerators (e.g., catalysts, calcium chloride, calcium formate), plasticizers, polymers, corrosion inhibitors, alkali-silica reactivity inhibitors, binders, colorants, defoamers, odor suppressants (e.g., fragrances), dry dispersants (i.e., those that improve the flow and wettability of dry materials when mixed with liquids).

[0106] In some embodiments, the repair mortar comprises about 45 vol.% to about 55 vol.% of one or more fillers. In some embodiments, the repair mortar comprises about 0.03 vol.% to about 0.3 vol.% of one or more chemical admixtures. In some embodiments, the repair mortar comprises about 45 vol.% to about 55 vol.% sand. In some embodiments, the repair mortar comprises about 3.5 vol.% to about 10 vol.% silica fume.

[0107] Due to the WRV of cellulose fibrils, the repair mortars described herein may not require a water retention agent. However, in some embodiments, the repair mortars described herein include one or more water retention agents (also known as thickeners or viscosity-modifying admixtures). Examples of water retention agents include (but are not limited to) high molecular weight copolymers (e.g., hydroxypropyl methylcellulose (HPMC), hydroxyethyl methylcellulose (HEMC), welan gum, xanthan gum, etc.). In some embodiments, the repair mortar includes 0 wt% of one or more water retention agents. In some embodiments, the repair mortar includes 0 wt% to about 0.08 wt% of one or more water retention agents. In some embodiments, the repair mortar includes about 0.03 wt% to about 0.08 wt% of one or more water retention agents.

[0108] A method 100 for obtaining a repair mortar 70 according to an exemplary embodiment of the present invention is shown in FIG. 2. In step 110, a cement binder 10 is mixed with a liquid 20 (e.g., water) to obtain a workable cementitious material 30. In some embodiments, one or more fillers and / or chemical admixtures and / or water retention agents 40 may be mixed with the cement binder 10 in a dry or liquid state. For example, in optional step 120, one or more fillers and / or chemical admixtures and / or water retention agents 40 may be mixed with the dry cement binder in a dry state. One or more fillers and / or chemical admixtures and / or water retention agents 40 may be mixed with the workable cementitious material 30 in a dry state in optional step 130. One or more fillers and / or chemical admixtures and / or water retention agents 40 may be mixed individually or collectively with a liquid 25 (e.g., water) in step 150, and the resulting liquid mixture(s) added to the workable cementitious material 30 in step 140. A dry cement binder may alternatively be added to the liquid mixture of one or more fillers and / or chemical admixtures and / or water retention agents in step 180 to obtain the workable cementitious material 30.

[0109] The cellulose fibrils 50 are mixed with the workable cementitious material 30 at step 160. In some embodiments, the cellulose fibrils 50 are mixed with a liquid 60 (e.g., water) to disperse the fibrils. The dispersed cellulose fibril slurry is then added to the workable cementitious material 30 at step 160 and mixed to obtain the cellulose fibril reinforced cement-based repair mortar 70. In some embodiments, the dry cellulose fibrils 50 are mixed with the workable cementitious material at step 170. In some embodiments, the dry cellulose fibrils 50 are mixed with one or more of the dry cement binder 10, dry filler(s) and / or chemical admixture(s) and / or water retention agent(s) 40 at step 190. In some embodiments (not shown), the dried cellulose fibrils 50 and / or the dispersed cellulose fibril slurry are mixed with a liquid mixture of one or more of the filler(s), chemical admixture(s), and water retention agent(s). In some embodiments, a pan mixer and / or drum mixer is used to mix the various components into the liquid 20.

[0110] The method of mixing the repair mortar 70 can affect the distribution of the cellulose fibrils throughout the repair mortar. For example, adding a thoroughly mixed aqueous suspension of cellulose fibrils 50 to a thoroughly mixed workable cementitious material 30 results in a uniform distribution of the cellulose fibrils 50 throughout the repair mortar. In some embodiments, the dry cellulose fibrils are thoroughly mixed with the workable cementitious material 30 (with or without dry filler(s) and / or chemical additive(s) and / or water retention agent(s)). In some embodiments, the dry cellulose fibrils are thoroughly mixed with the dry cement binder 10 and / or dry filler(s) and / or chemical additive(s) and / or water retention agent(s) 40.

[0111] In some embodiments, the repair mortar 70 is used to repair cracked or deteriorated concrete substrates and / or to fill pores in porous concrete substrates. The concrete substrate may be reinforced or unreinforced. For example, the concrete substrate may be reinforced with steel fibers and / or steel reinforcing bars (i.e., rebar). In some embodiments, the surface of the concrete substrate to be repaired is pretreated. For example, the surface of the concrete substrate to be repaired may be at least partially saturated with a liquid (e.g., water) and / or dust and / or debris may be removed. In some embodiments, the surface of the concrete substrate is pretreated by scarifying and / or roughening prior to application of the repair mortar 70. Because the cellulose fibrils can be added to a workable cementitious material, no new equipment and / or modifications to existing equipment are required.

[0112] 3 shows the hydration area 310 of conventional pulp fiber 300 and the hydration area 330 of cellulose fibril 320. The hydration area of ​​cellulose fibril is several orders of magnitude larger than that of conventional pulp fiber, thereby increasing the internal hardening area of ​​the repair mortar described herein. Because the cellulose fibril increases the internal hardening area of ​​the repair mortar by several orders of magnitude, the cellulose fibril reinforced repair mortar described herein dramatically improves the adhesive strength of the repair mortar-concrete substrate interface compared to conventional non-fibrillated pulp fiber reinforced cement-based repair mortar.

[0113] The water retention and desorption properties of cellulose fibrils allow them to regulate moisture during cement hardening, reducing and / or preventing early autogenous shrinkage problems caused by cement hydration. The retention of liquid by cellulose fibrils maintains the internal relative humidity of the repair mortar. Thus, liquid that would normally bleed and evaporate to the exposed surface of the repair mortar in the absence of cellulose fibrils is retained by the cellulose fibrils and gradually desorbs. The reduced bleeding minimizes and / or prevents early volume change induced microcracking. The cellulose fibrils distribute water evenly throughout the repair mortar matrix, maintaining hydration of the cement particles during hardening. The cellulose fibrils remain evenly distributed throughout the matrix of the repair mortar during hardening, which indicates reduced settling and / or bleeding compared to pulp fibers in non-fibrillated pulp fiber reinforced cement-based repair mortars. Without being bound by theory, it is speculated that this reduction in bleeding may be due to a reduction in the amount of free water in the workable cellulose fibril reinforced repair mortar. Reducing the volume change and / or maintaining the internal relative humidity and / or increasing the cement particle hydration of the cellulose fibril reinforced repair mortar described herein enhances the bond strength at the repair mortar-concrete substrate interface and / or reduces early shrinkage induced microcracking.

[0114] In some embodiments, the setting / hardening period of the cellulose fibril reinforced cement-based repair mortar is similar to the setting / hardening period of a conventional cement-based mortar. EXAMPLES

[0115] Example 1 The adhesive strength of the exemplary cellulose fibril reinforced repair mortar at the repair mortar-concrete substrate interface was evaluated using the diagonal shear test of American Society for Testing and Materials ("ASTM") C882 (2013). Four 75 mm x 280 mm cylindrical specimens were prepared and tested, including half cylinders of cement-based repair mortar and concrete substrate. A longitudinal cross-sectional view of an exemplary specimen 200 is shown in FIG. 4. The exemplary cylindrical specimen 200 includes a concrete substrate half cylinder 210 and a cement-based repair mortar half cylinder 220. The composition of the repair mortar and concrete substrate for each specimen is shown in Table 1. The cement binder was mixed with fine aggregate and water to obtain a workable cementitious material. The cellulose fibrils used in this test were produced by multi-stage refining of bleached kraft pulp at 30% consistency. After refining, the resulting cellulose filaments were thoroughly redispersed in water and then final dewatered to about 10% consistency. Cellulose fibrils are materials with a nano-width / micro-length size distribution. In some embodiments, the size distribution is 80-500 nm in width, 100-800 μm in length, and has a surface area of ​​about 80 m. 2 / g. The cellulose fibril slurry was mixed with a workable cementitious material to substantially uniformly distribute the cellulose fibrils throughout the workable cementitious material. To reduce or eliminate the mismatch (i.e., stiffness mismatch) between the repair mortar and the substrate, the composition of the repair mortar was selected such that the stiffness of the repair mortar substantially corresponds to the stiffness of the substrate. One skilled in the art will appreciate that the stiffness of the repair mortar / substrate is a function of the composition of the repair mortar / substrate. [Table 1-1] [Table 1-2]

[0116] To prepare each test specimen, a half-cylinder concrete substrate was mixed, cast into a form, and covered with a polyethylene sheet for 24 hours. Each concrete substrate was compacted in two layers (i.e., the half-cylinder form was half-filled with fresh concrete substrate mixture, vibrated using a vibrating table to remove trapped air, filled with fresh concrete substrate mixture, and then vibrated again). After demolding, the half-cylinder was wet-cured in a curing chamber at 23°C and 95% relative humidity (RH) for 14 days according to ASTM C192 / C192M-18 "Standard Practice for Making and Curing Concrete Test Specimens in Laboratory". The elliptical contact surface of the concrete substrate half-cylinder was pretreated with template-controlled surface roughening. Template-controlled surface roughening is a simple pretreatment method to ensure uniform substrate roughness. Before pouring the concrete substrate, a perforated steel plate with 7.5 mm x 1.4 mm openings was attached to the form insert to create uniformly distributed protrusions on the substrate surface after the casting and demolding operations. The concrete substrates, which had already been wet-cured, were then cleaned and inserted into the form again. Repair mortar was applied to each concrete substrate, and the repair mortar was compressed in two layers as described above. The specimens were covered with polyethylene sheets for 24 hours and wet-cured in lime water (as described above) at 23°C and 95% RH for 6 days. The specimens were each subjected to a pure compression test under a loading rate of 0.24 MPa / s using a Baldwin Tate-Emry compressive strength tester (manufactured by Baldwin Lima Hamilton Corporation, Ohio, USA) with a capacity of 400,000 pounds (i.e., a compressive force was applied to each specimen until failure was observed along the adhesive interface (i.e., the substrate-repair mortar interface). In all specimens, failure occurred at the repair mortar-concrete substrate interface.

[0117] Equations (1)-(3) were used to calculate the different stresses occurring during the test.

number

[0118] The diagonal shear test results of the specimens with steel reinforced concrete substrate and controlled bond area surface roughness (i.e., mixes 1 and 2 shown in Table 1) are shown in Figure 5. The diagonal shear test results of the specimens with unreinforced concrete and controlled bond area surface roughness are shown in Figure 6. The cement-based repair mortar of the specimens was reinforced with 0.1 vol.% cellulose fibrils (hatched bars) or not (black bars). The specimens with cellulose fibril reinforced cement-based repair mortar have obvious improvement in interfacial bond strength compared to the unreinforced specimens. The relative bond strength enhancement percentage in the 0.5% steel fiber reinforced specimens is only about 20.7%, while the unreinforced cellulose fibril reinforced specimens are enhanced by about 43%. Typically, the tendency of unrestricted nonlinear deformation of the repair mortar is higher in the case of unreinforced substrate. Therefore, the improvement in bond strength of the cellulose fibril reinforced specimens is emphasized when the specimens are without steel fiber reinforcement.

[0119] Images of the specimens after the pure compression tests are shown in Figures 7 and 8. Because one of the half-cylinder specimens broke, only seven specimens are shown in Figure 7, even though eight half-cylinder specimens (i.e., four cylinder specimens) were prepared. The specimens in Figure 7 contain the composition of Mix 2 shown in Table 1. The specimens in Figure 8 contain the composition of Mix 1 shown in Table 1. The greater degree of surface scarification observed in the cellulose fibril reinforced specimens shown in Figure 8 suggests that the cellulose fibril reinforced cement-based repair mortar produces a more compact repair mortar-substrate interfacial bond than the reference repair mortar (i.e., without cellulose fibrils).

[0120] Diagonal shear tests were also conducted to evaluate the effect of cellulose fibrils on the bond strength between the repair mortar / concrete substrate interface in the absence of pretreatment of the concrete substrate surface. Four 75 mm × 280 mm cylindrical specimens were prepared and tested, including half cylinders of cement-based repair mortar and concrete substrate. The compositions of the repair mortar and concrete substrate for each specimen are shown in Table 2. The cement binder was mixed with water to obtain a workable cementitious material. The cellulose fibrils were mixed with water to obtain a cellulose fibril slurry. The cellulose fibril slurry was mixed with the workable cementitious material to substantially uniformly distribute the cellulose fibrils throughout the workable cementitious material. The results of the diagonal shear tests are shown in Figures 9 and 10. The cement-based repair mortar of the specimens was either reinforced (hatched bars) or not reinforced (black bars) with 0.1 vol.% cellulose fibrils. [Table 2-1] [Table 2-2]

[0121] For the reinforced concrete substrate specimens (Figure 9), a slight decrease in bond strength was observed for the untreated unreinforced specimens compared to the surface-pretreated unreinforced specimens (Figure 5). Compared to the untreated 0.50% fiber-reinforced substrate covered with unreinforced repair mortar, the shear bond strength of the cellulose fibril-reinforced repair mortar-0.50% fiber-reinforced substrate composite increased by about 56% (Figure 9). For the unreinforced concrete substrate specimens (Figure 10), the bond strength was observed to increase by about 63% for the untreated cellulose fibril-reinforced specimens compared to the untreated unreinforced specimens (Figure 10). Since the roughened (i.e., pretreated) surface typically acts to enhance the mechanical bond between the repair mortar and the concrete substrate, a reduction in bond strength is expected for the untreated (i.e., smooth) specimens. Therefore, it is unclear why an enhancement in bond strength was observed with the cellulose fibril-reinforced specimens. Without wishing to be bound by theory, it is speculated that for smooth concrete substrate surfaces, hydration is maintained by cellulose fibrils that are uniformly distributed at the repair mortar-substrate interface.

[0122] Images of the specimens after pure compression testing (i.e., mixes 3 and 4 listed in Table 2) are shown in Figures 11 and 12. The specimen in Figure 11 contains the composition of mix 4 listed in Table 2. The specimen in Figure 12 contains the composition of mix 3 listed in Table 2. The greater degree of surface scarification observed in the cellulose fibril reinforced specimens shown in Figure 12 suggests that the cellulose fibril reinforced repair mortar produces a more compact repair mortar-substrate interfacial bond than the reference repair mortar (i.e., no cellulose fibrils).

[0123] Compared to the diagonal shear test results of the steel fiber reinforced concrete substrate covered with unreinforced repair mortar and subjected to surface roughening pretreatment by template control, the shear bond strength was observed to increase by about 21% for the cellulose fibril reinforced composites incorporating the fiber reinforced substrate (Figure 5). Compared to the diagonal shear test results of the specimens of the unreinforced concrete substrate covered with unreinforced repair mortar and subjected to surface roughening pretreatment by template control, the diagonal shear bond strength was observed to increase by about 43% for the corresponding cellulose fibril reinforced specimens (Figure 6). The effect of cellulose fibrils on the interfacial bond strength is even more evident in the specimens without concrete substrate surface pretreatment (i.e., smooth surface concrete substrate). Compared to the diagonal shear test results of the specimens of the unreinforced steel fiber reinforced concrete substrate covered with unreinforced repair mortar, the diagonal shear bond strength was observed to increase by about 56% for the cellulose fibril reinforced specimens (Figure 9). Compared with the diagonal shear test results of specimens covered with unreinforced repair mortar on untreated unreinforced concrete substrate, an increase of about 63% in diagonal shear bond strength was observed for the cellulose fibril reinforced specimens (Figure 10). Thus, the interfacial bond strength is enhanced by the cement-based repair mortar containing cellulose fibrils.

[0124] Example 2 The effect of unreinforced and cellulose fibril reinforced repair mortar overlays on the corrosion of steel rebars was evaluated. Specifically, the steel reinforcement corrosion risk was investigated in two types of rebar placements in the repair composites: steel rebars fully encapsulated in the concrete matrix / repair mortar overlay and steel rebars placed directly at the matrix-overlay interface. The corrosion performance of the steel rebars was monitored by measuring the corrosion current, time to initial crack formation in the specimens, surface crack width development, corrosion rate, and residual pull-out strength of the corroded rebars.

[0125] Ordinary Portland cement (OPC), natural sand, fine aggregate and 12 mm size crushed stone coarse aggregate (specific gravities 2.65 and 2.70, respectively) were used. The cellulose fibrils used in this study were produced by multi-stage refining of bleached kraft pulp at 30% consistency. After refining, the resulting cellulose filaments were fully redispersed in water and then finally dehydrated to about 10% consistency. Cellulose fibrils are a material with a nano-width / micro-length size distribution. In some embodiments, the size distribution is 80-500 nm in width, 100-800 μm in length, and has a surface area of ​​about 80 m 2 / g. 10M deformed carbon steel rebar and 13mm brass coated steel microfiber (Dramix OL 13 / 0.20) were used. Other materials utilized in the mix preparation were Darex II air entraining admixture (AEA) and ADVA CAST 575 high-range water reducing admixture (HRWR). Pictorial representations of the cellulose fibrils and steel fibers utilized in this study are shown in Figures 13(a)-13(b).

[0126] To minimize the modulus mismatch between the concrete substrate and the repair mortar overlay, and the poor dispersion of cellulose fibrils in the repair mortar mixture, trial batches of different classes of concrete and repair mortar mixture were prepared and evaluated. Based on the preliminary results, two types of mixtures, consisting of concrete with a water-cement (w / c) ratio of 0.45 for the substrate and a repair mortar overlay mixture with a w / c ratio of 0.40, were prepared in the mix proportions shown in Table 1 and used in the main tests. Some substrates were unreinforced, while others were reinforced with 0.50% steel fibers. The unreinforced and cellulose fibril reinforced repair mortar mixtures were reinforced with 0% and 0.1% volume fractions, respectively. To make a fair comparison between the mixtures, the w / c ratio of the mixtures was kept constant by reflecting the moisture content of the cellulose fibril slurry in the mix design. In all tests, the repair mortar overlay was cast 24 hours after the substrate was cast. Afterwards, the composite specimens were subjected to additional wet curing at a temperature of 23 °C and 95 ± 5% RH for 13 days before the relevant tests were carried out. [Table 3]

[0127] Accelerated corrosion tests of rebar were carried out to evaluate the corrosion protection of steel reinforcement in unreinforced and 0.5% steel fibre concrete substrates covered with unreinforced and cellulose fibril reinforced repair mortars. Two sets of specimens were tested. Figures 14(a) and 14(b) show a typical illustration for the first set of corrosion specimens (100mm x 200mm composite cylinders), while the illustration for the second set of specimens (200mm x 100mm x 50mm bonded prisms) is shown in Figures 23(a) and 23(b). For each repair substrate-overlay type considered, three specimens were tested.

[0128] Before embedding the uncorroded deformed (ribbed) steel reinforcing bars into the substrate, the reinforcing bars were thoroughly washed using acetic acid solution and the initial mass was quantified. 24 hours after casting, the overlay was cast onto the substrate. The demolded composites were then wet cured for another 13 days. The first set of cylindrical specimens was partially immersed to half height in a container of 5% NaCl aqueous solution and an applied voltage of 25 V was applied to accelerate the corrosion process for 14 days. Meanwhile, to evaluate the effect of different corrosion degrees on the performance of steel reinforcing bars placed directly at the concrete substrate-repair mortar overlay interface, prismatic specimens were tested using variable applied voltages of 7.5 V, 15 V, and 25 V for test periods of 21 days, 14 days, and 8 days, respectively. Figure 15 shows the accelerated corrosion test setup. For each specimen, monitoring of corrosion-induced crack width propagation began once crack initiation was visually observed during the test. Images of the longitudinal cracks in the specimens were taken with a high-resolution digital camera every day until the end of the test period. These images were then processed using open-source image analysis software. At the end of the accelerated corrosion test, the extracted reinforcements were cleaned with a wire brush and then left in an aqueous acetic acid solution for 24 hours. The reinforcements were then brushed again, dried, gently sandblasted using 85 psi pressure, and weighed. The same cleaning technique was used for all reinforcing bars. The actual mass loss of the reinforcing bars was used to calculate the rebar corrosion rate in each repair system using Equation 6: ASTM G1-03 (2017).

number

[0129] Figures 16(a)-16(c) show typical image profiles of the cylindrical specimens after corrosion testing. In all tested specimens, steel rebar corrosion-induced cracks in the specimens occurred longitudinally in the vicinity of the embedded steel rebars. Similarly, the corrosion residues (oxides) observed in the split specimens were generally less in the specimens incorporating cellulose fibril reinforced repair mortar (Figure 16(c)) than in the specimens without CMF (Figure 16(b)).

[0130] The average steel rebar corrosion currents in the plain substrate-repair mortar overlay composites and the steel fiber reinforced substrate-repair mortar overlay composites are shown in Figures 17 and 18, respectively. From Figure 17, it is quite clear that the corrosion activity is reduced in the composite cylinders incorporating cellulose fibril reinforced repair mortar. Figure 17 shows that the initial current for both sets of plain substrates covered with unreinforced or cellulose fibril reinforced repair mortar was about 0.1 A, but as an oxidation layer formed on the reinforcing bars, the corrosion current decreased until the expansion stress from the rust layer caused microcracks at the rebar-matrix interface. Compared to the repair composites prepared with unreinforced repair mortar, the repair systems prepared with cellulose fibril reinforced repair mortar showed a slower cracking of the matrix and the resulting increase in test solution inflow and corrosion current. Conversely, Figure 18 shows a slightly different trend in the steel fiber reinforced substrate-repair mortar overlay specimens. First, the addition of steel fibers to the substrate increased the initial corrosion current of the specimens. The increase in current is attributed to the ability of the brass-coated microfibers randomly distributed in the substrate to enhance the substrate's electrical conductivity. Although the corrosion activity was rapid in both sets of repair specimens compared to the plain substrate-repair mortar overlay composite, the composites using cellulose fibril-reinforced repair mortar as the overlay material seemed to show less severe specimen degradation.

[0131] The time to initiation of microcracks near the interface between the corroded steel rod and the adjacent matrix for the cylindrical composite specimens is shown in Figure 19. The results shown in Figure 19 indicate that microcracks occurred earlier in the composite specimens prepared with unreinforced repair mortar as an overlay for both the plain and steel fiber reinforced substrates. It is also evident from Figure 19 that the addition of brass-coated steel microfibers to the substrate accelerated crack initiation in two sets of repair composites, with the effect being more severe for the unreinforced repair mortar overlay.

[0132] Figure 20 shows the evolution of surface crack widths for cylindrical composite specimens. Although the steel fibers increased the electrical conductivity of the specimens, making them more susceptible to initial crack initiation, the crack bridging ability of such fibers helped minimize the propagation of crack widths in the specimens. Thus, in the two sets of repair composites, the average maximum crack widths at the end of the test were smaller compared to those observed in the composite specimens prepared with unreinforced substrates. The most important inference from Figure 20 is that the crack widths were reduced by approximately 31-37.5% with the cellulose fibril reinforced repair mortar overlay compared to the unreinforced repair mortar overlay. This improvement in crack control observed in the composite specimens incorporating the cellulose fibril reinforced repair mortar is attributed to two factors. First, the amount of rebar corrosion by-products generated in the specimens was reduced, ultimately leading to a reduction in the expansion pressure that propagated the cracks. Second, compared with the non-reinforced repair mortar overlay, the bonding between the cellulose fibril-reinforced repair mortar overlay and the substrate was improved, which may have reduced the movement of the cracked overlay by the substrate.

[0133] Using the actual corrosion-induced rebar mass loss, the rebar corrosion rates in the two sets of repair composites were calculated and shown in Figure 21. The use of cellulose fibril-reinforced repair mortar slightly reduced the corrosion rate of the steel reinforcement in the composites, especially in the composites prepared with unreinforced substrate. The rebar pull-out results before and after the accelerated corrosion test are shown in Figure 22. The first finding from Figure 22 is that although the ultimate pull-out strength is only slightly enhanced by the addition of steel fibers to the substrate, the effect of the steel fibers becomes more evident after the steel reinforcing bars are partially degraded. Meanwhile, the superior containment provided by the cellulose fibril-reinforced repair mortar resulted in better pull-out performance than the unreinforced repair mortar for both corroded and uncorroded steel bars.

[0134] Several images of the corrosion test prisms (unreinforced substrate-repair mortar overlay) after 15V and 25V accelerated corrosion tests are shown in Figures 24(a)-24(e). Figures 24(a)-24(c) show the results of the 15V corrosion test, while Figures 24(d) and 24(e) show the results of the 25V corrosion test. Figure 24(a) confirms that the accumulation of corrosion by-products at the substrate-overlay interface will eventually lead to repair failure over time. It is also evident from Figures 24(b) and 24(c) that corrosion of the steel rebar was somewhat reduced in the prisms incorporating the cellulose fibril reinforced repair mortar as an overlay. However, Figures 24(d) and 24(e) show that the benefits arising from the use of the cellulose fibril reinforced repair mortar are diminished as the corrosion rate increases significantly. This is understandable considering that the high applied voltage, increased rebar corrosion rate, and accumulation of by-products partially obscure the matrix transport / permeability and adhesive strength advantages produced by the cellulose fibril reinforced repair mortar overlay.

[0135] The average corrosion currents measured for the repair composites, in which steel reinforcing bars were sandwiched between the plain concrete substrate and the repair mortar overlay, are shown in Figures 25 and 26. Figure 25 shows that, although a very low level of rebar corrosion was induced at an applied voltage of 7.5 V, a slight difference in performance was still discernible between the unreinforced and cellulose fibril-reinforced repair mortars, with the latter showing a slightly lower corrosion current. However, so little corrosion occurred on the test prisms that the specimens did not crack even after 21 days. Conversely, when the applied voltage was increased to 15 V, Figure 26 highlights a clear difference in the response of the two sets of repair materials. Not only did the specimens covered with the unreinforced repair mortar crack faster, but they also showed faster crack opening and current development. A similar trend was also highlighted in Figure 27 when the applied voltage was increased to 25 V. However, accelerating the corrosion process using 25V induced significant corrosion rates, partially compromising the effectiveness of the steel rebar protection by the cellulose fibril reinforced repair mortar overlay. Nevertheless, it is very clear from Figure 27 that the corrosion performance of the steel reinforcing bar located at the substrate-repair overlay interface is better when the overlay is made of cellulose fibril reinforced repair mortar.

[0136] The average time required for the initial microcracks to develop in the test prisms is shown in Figure 28. No cracks were observed in the specimens when an applied voltage of 7.5 V was used, whereas the crack initiation time for an applied voltage of 15 V was 229 hours for the plain substrate-unreinforced repair mortar overlay and 237 hours for the plain substrate-cellulose fibril reinforced repair mortar overlay. A further increase in the applied voltage to 25 V caused the microcracks to develop more rapidly, but a similar trend to the 15 V test was also observed. The microcrack initiation time for the 25 V accelerated test was 82 hours for the substrate-unreinforced repair mortar overlay and 89 hours for the substrate-cellulose fibril reinforced repair mortar overlay. Comparing these results to those of the cylinder repair composites tested at the same applied voltage of 25 V, it is clear that failure was initiated earlier in the prism composites. This is not surprising considering that the steel rebar in the cylindrical specimens was completely encapsulated by the concrete substrate and repair mortar overlay, whereas in the prism specimens, the steel rebar was located at the substrate-overlay interface, allowing easier access to the test solution and oxygen. Furthermore, compared to the substrate / overlay matrix, the interface is more prone to widening when the expansion stresses from corrosion by-products exceed the substrate-overlay bond strength.

[0137] Figure 29 shows the corrosion rate of the steel rebar calculated from the actual mass loss recorded at the end of each test, and as expected, the corrosion rate of the repair composite incorporating cellulose fibril reinforced repair mortar as an overlay was lower. In the 15V accelerated corrosion test, the corrosion rate was reduced from 5.4 mm / year to 1.8 mm / year compared to the unreinforced repair mortar composite. However, in the 25V test, the corrosion rate increased sharply to about 20 mm / year for the substrate-unreinforced repair mortar overlay and 13.0 mm / year for the substrate-cellulose fibril reinforced repair mortar overlay. The main inference from these results is that for light or moderate levels of corrosion, the cellulose fibril reinforced repair mortar is quite effective in minimizing the deterioration of the steel reinforcing bars and the occurrence of general corrosion.

[0138] The results of the residual rebar pull-out force are shown in Figure 30. This figure shows that the rebar pull-out resistance generally decreases with increasing corrosion levels. This is expected considering that higher levels of rebar corrosion result in increased loss of rebar cross section and brittle rust deposits adjacent to the steel rebar. Thus, the lower pull-out resistance observed is a result of reduced mechanical and frictional resistance of the rebar, as well as increased delamination at the substrate-overlay interface. Notwithstanding the above, the residual rebar pull-out force of composites incorporating cellulose fibril reinforced repair mortar overlay was superior to composites prepared with unreinforced repair mortar at all corrosion levels evaluated.

[0139] Results on steel reinforcing bars embedded in unreinforced or steel fiber reinforced concrete cylinders prior to further encapsulation with a repair mortar overlay showed that the cellulose fibril reinforced repair mortar provided superior resistance to chloride ingress and rebar corrosion. Thus, specimens incorporating cellulose fibril reinforced repair mortar not only delayed microcracking of the repair composite, but also reduced average crack width and corrosion rate compared to specimens prepared with unreinforced repair mortar.

[0140] The addition of brass-coated steel microfibers to the substrate accelerated crack initiation in both sets of repair composites studied, but this adverse effect was more severe in the case of the fiber-reinforced substrate-unreinforced repair mortar composite. However, the steel microfibers were not only effective in reducing crack width propagation and test fluid ingress, but also reduced the rebar corrosion rate in the repair composites. Furthermore, the positive effect of the steel fibers on the rebar pull-out resistance became more evident after corrosion-induced cross-sectional loss occurred in the steel reinforcing bars.

[0141] For reinforcing bars placed at the substrate-overlay interface, it was confirmed that the accumulation of corrosion by-products at the substrate-overlay interface would eventually lead to repair failure over time. However, the test results also showed that the use of cellulose fibril-reinforced repair mortar as an overlay material provided superior protection against rebar corrosion. The aforementioned enhanced protection provided by cellulose fibril-reinforced repair mortar was more effective at light or moderate levels of corrosion activity.

[0142] Despite the fact that the pull-out resistance of the corroded rebar generally decreased when the applied voltage used to accelerate the corrosion process was increased from 7.5 to 25 V, the pull-out strength of the remaining corroded rebar in composites incorporating cellulose fibril reinforced repair mortar was better than that of the substrate covered with the corresponding unreinforced reference repair mortar.

[0143] While a number of exemplary aspects and embodiments have been discussed above, those of ordinary skill in the art will recognize certain modifications, permutations, additions, and subcombinations thereof, and as such, it is intended that the following appended claims, and any claims hereafter introduced, be interpreted to include all such modifications, permutations, additions, and subcombinations consistent with the broadest interpretation of the specification as a whole.

[0144] Interpretation of Terms Unless the context clearly requires otherwise, throughout this specification and claims: The words "comprise", "comprising" and the like shall be construed in their inclusive sense and not in their exclusive or exhaustive sense, i.e. "including, but not limited to". When used to describe this specification, the words "herein," "above," "below," and words of similar import shall refer to this specification as a whole and not to any particular portions of the specification. · "Or", when referring to a list of two or more items, covers all of the following interpretations of the word: any of the items in the list, all of the items in the list, and any combination of the items in the list. The singular forms "a", "an" and "the" include any appropriate plural references.

[0145] Where a component (e.g., a substrate, assembly, device, manifold, etc.) is referred to above, unless otherwise indicated, the reference to that component (including the reference to "means") should be interpreted as including any components that perform the function (i.e., are functionally equivalent) of the described component as equivalents of that component (including components that are not structurally equivalent to the disclosed structures that perform the function in the illustrated exemplary embodiments described herein).

[0146] Specific examples of systems, methods, and devices have been described herein for illustrative purposes. These are examples only. The techniques presented herein may be applied to other than the exemplary systems described above. Many changes, modifications, additions, omissions, and permutations are possible within the practice of the invention. The invention includes variations of the described embodiments that will be apparent to those skilled in the art, including variations obtained by: replacing features, elements, and / or acts with equivalent features, elements, and / or acts; mixing and matching features, elements, and / or acts of different embodiments; combining features, elements, and / or acts of the embodiments described herein with features, elements, and / or acts of other technologies; and / or omitting combinations of features, elements, and / or acts of the described embodiments.

[0147] It is therefore intended that the following appended claims and any claims hereafter introduced be interpreted to include all such modifications, permutations, additions, omissions, and subcombinations that may reasonably be construed. The scope of the claims should not be limited by the preferred embodiments set forth in the examples, but should be accorded the broadest interpretation consistent with the description as a whole.

Claims

[Claim 1] A method for improving the corrosion resistance of reinforcing steel in a concrete material using a repair mortar, comprising: obtaining a cracked and / or damaged concrete material having rebars at least partially embedded therein; mixing a cement binder and fine aggregate with cellulose fibrils to uniformly disperse the cellulose fibrils, thereby obtaining a mixture of the cement binder, the fine aggregate, and the cellulose fibrils; further mixing the mixture with a water / chemical admixture to obtain a workable repair mortar; applying the workable repair mortar to the concrete material; The cellulose fibrils constitute about 0.1 vol. % of the repair mortar after drying, and the surface area of ​​the cellulose fibrils is 60 to 100 m 2 / g, the cellulose fibrils have a width of about 80 nm to about 500 nm and a length of about 100 μm to about 800 μm, and at least 95% of the cellulose fibrils have an aspect ratio of at least 50.

Citation Information

Patent Citations

  • Method for reducing shrinkage and cracking of mortar or concrete due to drying

    JP1998029847A

  • Construction material

    JP2017024938A

  • Mortar composition

    JP2018030744A

  • Cementitious inorganic material containing cellulosic nanofibers

    US20190062211A1